2018
DOI: 10.1080/21645515.2018.1526588
|View full text |Cite
|
Sign up to set email alerts
|

Viral etiological causes of febrile seizures for respiratory pathogens (EFES Study)

Abstract: Background: Febrile seizure is the most common childhood neurological disorder, is an important health problem with potential short-and long-term complications, also leading to economic burden and increased parental anxiety about fevers and seizures occurring in their children. There are no routine recommendation to detect etiological causes of FS for neurological perspective, further knowledge about the etiological causes of FS in children will support preventive measures and follow-up strategies. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 30 publications
7
58
1
2
Order By: Relevance
“…5 Most febrile seizures occur in the setting of viral infections; most commonly adenovirus, followed by influenza, rhinovirus, and RSV with coronavirus OC43 are detected in children younger than 12 months old. 6 Our patient had COVID-19 in addition to rhinovirus confirmed on high throughput sequencing. Interestingly, a study of coronavirus-positive infants in the first 6 months of life noted a 27% coinfection rate with rhinovirus.…”
Section: Discussionmentioning
confidence: 62%
“…5 Most febrile seizures occur in the setting of viral infections; most commonly adenovirus, followed by influenza, rhinovirus, and RSV with coronavirus OC43 are detected in children younger than 12 months old. 6 Our patient had COVID-19 in addition to rhinovirus confirmed on high throughput sequencing. Interestingly, a study of coronavirus-positive infants in the first 6 months of life noted a 27% coinfection rate with rhinovirus.…”
Section: Discussionmentioning
confidence: 62%
“…Unlike SARS- and MERS-CoV, which are known to cause more sporadic outbreaks, the other four human CoV are endemic causing annual widespread morbidity in infants and the elderly, potentially requiring hospitalization. ( Carman et al, 2018 ; Falsey et al, 2002 ; Varghese et al, 2018 ). Although rare, endemic human CoV like HCoV-229E and HCoV-OC43 can also cause severe respiratory disease (pneumonia, ARDS, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…asthma, COPD) and the elderly ( Dijkman et al, 2012 ; Falsey et al, 2002 ). In children, severe respiratory tract CoV infections require hospitalization in about 10% of cases and have been associated with febrile seizure in those less than 1 year old ( Carman et al, 2018 ; Heimdal et al, 2019 ). CoV infection can also be severe in the elderly requiring hospitalization and can even cause acute respiratory distress syndrome (ARDS) ( Falsey et al, 2002 ; Vassilara et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Another prospective multicenter study from Turkey included 192 children with febrile seizures and found that HCoV OC43 is the single most common, yet still rare, cause for febrile seizures in children under 12 months (6% of children under 12 months with febrile seizures were positive for OC43). 20 Finally, five case reports in children described the following neurological complications associated with the detection of coronavirus: acute flaccid paralysis, acute disseminated encephalomyelitis (ADEM), Guillain-Barr e syndrome (GBS) and two cases of fatal encephalitis (both in children with underlying immune deficiency), described in Table S4.…”
Section: Acute Infectionsmentioning
confidence: 99%